2018
DOI: 10.1590/1414-431x20186754
|View full text |Cite
|
Sign up to set email alerts
|

Human dental pulp stem cell adhesion and detachment in polycaprolactone electrospun scaffolds under direct perfusion

Abstract: Cell adhesion in three-dimensional scaffolds plays a key role in tissue development. However, stem cell behavior in electrospun scaffolds under perfusion is not fully understood. Thus, an investigation was made on the effect of flow rate and shear stress, adhesion time, and seeding density under direct perfusion in polycaprolactone electrospun scaffolds on human dental pulp stem cell detachment. Polycaprolactone scaffolds were electrospun using a solvent mixture of chloroform and methanol. The viable cell numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…When analyzing the pore size of the scaffold by SEM, a structure of micropores and macropores was observed with dimensions ranging from 73 µm to 124 µm and with an average size of 86 µm ( Figure 1 B). A crucial characteristic of a scaffold is the ability to have interconnected pores, which is favorable for cell adhesion and growth; however, extremely large pores can impair the vascularization of the biomaterial by making difficult contact between cells [ 41 ]. Majore et al [ 42 ] reported how the size of mesenchymal cells could vary from 11 to 19 µm and suggested how the size of the pores, presented in the scaffold developed, could be sufficient for cell growth, allowing the exchange of nutrients and metabolites between permeated cells within the material.…”
Section: Resultsmentioning
confidence: 99%
“…When analyzing the pore size of the scaffold by SEM, a structure of micropores and macropores was observed with dimensions ranging from 73 µm to 124 µm and with an average size of 86 µm ( Figure 1 B). A crucial characteristic of a scaffold is the ability to have interconnected pores, which is favorable for cell adhesion and growth; however, extremely large pores can impair the vascularization of the biomaterial by making difficult contact between cells [ 41 ]. Majore et al [ 42 ] reported how the size of mesenchymal cells could vary from 11 to 19 µm and suggested how the size of the pores, presented in the scaffold developed, could be sufficient for cell growth, allowing the exchange of nutrients and metabolites between permeated cells within the material.…”
Section: Resultsmentioning
confidence: 99%
“…138 In addition, some more complex dynamic mechanical behaviors play very important regulatory roles in the stem cell microenvironment maintenance, thus how to achieve accurate detection of these mechanical parameters is also the research direction of scientists. 139,140 4.2.3. Biological Factors.…”
Section: Acs Applied Bio Materialsmentioning
confidence: 99%
“…Equivalently, not only did the polylysine and 19-mer peptide bifunctional hydrogels prepared by Farrukh regulate the stiffness of the scaffolds by adjusting the proportions of the two components, thus promoting the differentiation of stem cells to varying degrees, but also it promoted the generation of β1-integrin in embryonic cortical neurons by the components synergy . In addition, some more complex dynamic mechanical behaviors play very important regulatory roles in the stem cell microenvironment maintenance, thus how to achieve accurate detection of these mechanical parameters is also the research direction of scientists. , …”
Section: Bioreactor Synergy With Scaffolds For Stem Cells Proliferati...mentioning
confidence: 99%
“…MSCs from exfoliated deciduous teeth were used in association with polycaprolactone electrospun scaffolds to study the effect of flow rate and shear stress, adhesion time and seeding density under direct perfusion in a bioreactor [ 21 ]. MSC derivates of exfoliated deciduous teeth modulated early astrocyte response after spinal cord contusion [ 22 ].…”
Section: Introductionmentioning
confidence: 99%